Current status of laboratory and imaging diagnosis of neonatal necrotizing enterocolitis - Gabriella D'Angelo; Pietro Impellizzeri; Lucia Marseglia; Angela Simona Montalto; Tiziana Russo; Ignazio Salamone; Raffaele Falsaperla; Giovanni Corsello; Carmelo Romeo; Eloisa Gitto (BMC, 2018)
Abstract Necrotizing enterocolitis continues to be a devastating disease process for very low birth weight infants in Neonatal Intensive Care Units. The aetiology and pathogenesis of necrotizing enterocolitis are not definitively understood. It is known that necrotizing enterocolitis is secondary to a complex interaction of multiple factors that results in mucosal damage, which leads to intestinal ischemia and necrosis. Advances in neonatal care, including resuscitation and ventilation support technology, have seen increased survival rates among premature neonates and a concomitant detection in the incidence of this intestinal disease. Diagnosis can be difficult, and identifying infants at the onset of disease remains a challenge. Early diagnosis, which relies on imaging findings, and initiation of prompt therapy are essential to limit morbidity and mortality. Moreover, early management is critical and life-saving. This review summarizes what is known on the laboratory and instrumental diagnostic strategies needed to improve neonatal outcomes and, possibily, to prevent the onset of an overt necrotizing enterocolitis.